2020
DOI: 10.4251/wjgo.v12.i8.903
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hyperthermic intraperitoneal chemotherapy regimens for treatment of peritoneal-metastasized colorectal cancer

Abstract: BACKGROUND Cytoreductive surgery (CRS) in combination with hyperthermic intraperitoneal chemotherapy (HIPEC) improves patient survival in colorectal cancer (CRC) with peritoneal carcinomatosis (PC). Commonly used cytotoxic agents include mitomycin C (MMC) and oxaliplatin. Studies have reported varying results, and the evidence for the choice of the HIPEC agent and uniform procedure protocols is limited. AIM To evaluate therapeutic benefits and complications of CRS + MMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…A study by Charrier et al showed that HIPEC-OXL increased the risk of postoperative bleeding compared with other agents (15.7% vs. 2.6%; p = 0.004) [183]. Similar results were found in a retrospective study, in which there was no difference in mOS between the two groups using MMC or OXL, patients treated with HIPEC-OXL had increased complication rates compared to those receiving MMC (66.2% vs. 35.3%; p = 0.003), especially bowel weakness, intra-abdominal infections, and urinary tract infections [184]. In contradiction, in the study by Delhorme et al, the DFS and peritoneal DFS (PDFS) were significantly better in the MMC group than the OXL group, and there was no difference in the OS and complication rates between the two groups [185].…”
Section: Ipcsupporting
confidence: 75%
“…A study by Charrier et al showed that HIPEC-OXL increased the risk of postoperative bleeding compared with other agents (15.7% vs. 2.6%; p = 0.004) [183]. Similar results were found in a retrospective study, in which there was no difference in mOS between the two groups using MMC or OXL, patients treated with HIPEC-OXL had increased complication rates compared to those receiving MMC (66.2% vs. 35.3%; p = 0.003), especially bowel weakness, intra-abdominal infections, and urinary tract infections [184]. In contradiction, in the study by Delhorme et al, the DFS and peritoneal DFS (PDFS) were significantly better in the MMC group than the OXL group, and there was no difference in the OS and complication rates between the two groups [185].…”
Section: Ipcsupporting
confidence: 75%
“…Dosage varied considerably for MMC (12.5-40 mg/ m 2 ) and OX (200-460 mg/m 2 ), which was combined with irinotecan in one of the studies. [24][25][26][27][28][29][30][31][32][33][34] Recently, Zhang et al performed a systematic review and meta-analysis of comparative studies regarding these two HIPEC regimens and concluded there was no survival benefit for either regimen over the other. Significantly more complications occurred in patients receiving OX-based HIPEC.…”
Section: Question 2: Role Of Hipec Using Mitomycin-c In Colorectal Ca...mentioning
confidence: 99%
“…Additional retrospective analyses have shown mixed results when evaluating the efficacy and safety profiles between these commonly used agents when treating CRC, but more studies demonstrate equivalent efficacy [ 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 ]. Further studies comparing oxaliplatin vs. MMC + doxorubicin [ 197 ], irinotecan vs. oxaliplatin [ 198 ], oxaliplatin ± irinotecan [ 181 , 199 ], and MMC vs. melphalan [ 200 ] have been performed but have not yielded a definitively superior regimen.…”
Section: Landmark Efficacy Studiesmentioning
confidence: 99%